Physicochemical and Sensory Analysis of Cocoa-Coffee Blend Drink Using the Check-All-That-Apply (CATA) - Cempaka, Laras; Annisaa, Dhita Noor; David, Wahyudi; Ramadhan, Kurnia (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2023)
Chocolate drinks are widely consumed due to their rich flavor and polyphenol content. Previous research has highlighted the flavor richness and high polyphenol content of Arabica coffee. This study aims to examine the effects of adding Arabica coffee on the physical characteristics and sensory profiles of chocolate drinks. The composition of the chocolate drinks used in this study includes fermented cocoa powder, Java Preanger Arabica coffee powder, Cascara Arabica, and stevia sweetener. Physicochemical analysis methods encompass color testing, pH measurement, and total soluble solids (TSS) determination. The five tested formulations resulted in a slightly dark yellowish-red color, with pH values ranging from 5.82 ± 0.10 to 6.22 ± 0.08, and TSS content ranging from 5.17 ± 0.76 to 5.90 ± 0.46. In addition to physicochemical analysis, sensory analysis was conducted using the Check-All-That-Apply (CATA) method facilitated by XLSTAT. Although no formulations matched the ideal product, the most preferred formulation consisted of 80% cocoa and 20% coffee, attributed to its sweet flavor. With lower percentages of coffee addition, attributes such as chocolate flavor, sweetness, caramel flavor, and milk flavor became more prominent in the chocolate drinks.